Author Correction: Germline HAVCR2 mutations altering TIM-3 characterize subcutaneous panniculitis-like T cell lymphomas with hemophagocytic lymphohistiocytic syndrome. (January 2019) - Gayden, Tenzin; Sepulveda, Fernando; Khuong-Quang, Dong-Anh; Pratt, Jonathan; Valera, Elvis; Garrigue, Alexandrine; Kelso, Susan; Sicheri, Frank; Mikael, Leonie; Hamel, Nancy; Bajic, Andrea; Dali, Rola; et al.
In the version of this article originally published, the main-text sentence "In three patients of European ancestry, we identified the germline variant encoding p.Ile97Met in TIM-3, which was homozygous in two (P12 and P13) and heterozygous in one (P15) in the germline but with no TIM-3 plasma membrane expression in the tumor" misstated the identifiers of the two homozygous individuals, which should have been P13 and P14. The error has been corrected in the HTML, PDF and print versions of the paper.